Системи управління регіонами в Давньому Китаї: досвід історичного моделювання - Величко, В. (Китаєзнавчі дослідження, 2011)
The paper presents the research of regional management performed by the central government rulers of ancient China (from Xia to Han dynasty). Using regional modeling concept proposed by J.Friedman for pre-industrial society the author has made an attempt to construct models of Center-Periphery relationship and features of each model.